The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1982
DOI: 10.1115/1.3253179
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Distributions in a Superlaminar Journal Bearing

Abstract: The main features of a comprehensive set of pressure measurements, obtained from a short, plain journal bearing, are presented. The pressure field in the lubricant film was measured in both the circumferential and axial directions over a Reynolds number range of 40–50,000. In cases where the film is noncavitating the pressure distributions are separated into viscous and inertial components. The inertial components are found to agree fairly well with an approximate short bearing theory. Axially averaged, total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Roberts and Hinton's (12) tests revealed that negative absolute pressures are more likely to occur at coupled superlaminar and high eccentricity operation or for very high values of Reynolds number, Re ≈ 11,800-44,600. However, operating with a high clearance, the bearing should entrain a lot of air, which should not permit negative absolute pressures to develop.…”
Section: Resultsmentioning
confidence: 97%
“…Roberts and Hinton's (12) tests revealed that negative absolute pressures are more likely to occur at coupled superlaminar and high eccentricity operation or for very high values of Reynolds number, Re ≈ 11,800-44,600. However, operating with a high clearance, the bearing should entrain a lot of air, which should not permit negative absolute pressures to develop.…”
Section: Resultsmentioning
confidence: 97%
“…The outlet boundary condition is set as free outflow, the flow is considered to be absolutely developed, the fixed wall boundary condition is selected as no slip wall. [37][38][39][40][41][42][43]…”
Section: Model and Numerical Methodsmentioning
confidence: 99%
“…It was concluded that although the fluid inertia has negligible effect on the load carrying capacity under laminar flow condition, it has a considerable effect on the stability of flow in journal bearings. Roberts and Hinton [5] found experimentally that the inertia effect is significant at low load condition. Gandjalikhan Nassab and Moayeri [6] studied the effect of inertia on hydrodynamic characteristics of long journal bearing using computational fluid dynamics (CFD) techniques.…”
Section: Introductionmentioning
confidence: 97%